The phylogeographic history of Krascheninnikovia reflects the development of dry steppes and semi-deserts in Eurasia - Anna Seidl (Nature Portfolio, 2021)
Abstract Constituting one of Earth’s major biomes, steppes are characterised by naturally treeless extra-tropical vegetation. The formation of the Eurasian steppe belt, the largest steppe region in the world, began in Central Asia during the Neogene. In the glacial stages of the Pleistocene, steppe displaced forest vegetation, which in turn recolonised the area during the warmer interglacial periods, thus affecting the distribution of plants adapted to these habitats. Krascheninnikovia ceratoides (Chenopodiaceae) is a plant characteristic of dry steppe and semi-desert formations. Earlier studies showed that the ancestor of this autochthonous steppe element originated in Central Asia during the Miocene/Pliocene, i.e., in the same region and at the same time as the first appearance of steppe vegetation. However, as the extant lineages of Krascheninnikovia ceratoides diversified only 2.2 ± 0.9 Mya, it may represent a modern element of current dry steppe and semi-desert formations, rather than a component of the first steppe precursors of the Miocene. As such, it may have capitalised on the climatic conditions of the cold stages of the Quaternary to expand its range and colonise suitable habitats outside of its area of origin. To test this hypothesis, phylogeographic methods were applied to high-resolution genotyping-by-sequencing data. Our results indicate that Krascheninnikovia originated in western Central Asia and the Russian Altai, then spread to Europe in the West, and reached North America in the East. The populations of eastern Central Asia and North America belong to the same clade and are genetically clearly distinct from the Euro-Siberian populations. Among the populations west of the Altai Mountains, the European populations are genetically distinct from all others, which could be the result of the separation of populations east and west of the Urals caused by the Pleistocene transgressions of the Caspian Sea.